$y=\frac{2(\tan x-1)}{\cos x-\sin x}$
$y=\frac{2(\tan x-1)}{\cos x-\sin x}$
y = 2·(TAN(x) - 1)/(COS(x) - SIN(x))
N(x)=2·(TAN(x) - 1) = 2·TAN(x) - 2 = N
D(x)=(COS(x) - SIN(x)) = D
y'=dy/dx=(N'D-ND')/D^2
-------------------------------------
N'= 2/COS(x)^2
D'= - COS(x) - SIN(x)
Inserisci e semplifica ottenendo alla fine:
- 2·SIN(x)/COS(x)^2
-------------------------
Pongo: Χ = COS(x), Υ = SIN(x) ed applico la regola di derivazione del rapporto (di sopra)
(2/Χ^2·(Χ - Υ) - 2·(Υ/Χ - 1)·(-Χ - Υ))/(Χ - Υ)^2=
=((2/Χ - 2·Υ/Χ^2) - (2·Χ - 2·Υ^2/Χ))/(Χ - Υ)^2=
=2·(Υ - Χ)·(Υ·Χ + Χ^2 - 1)/Χ^2/(Χ - Υ)^2=
=2·(Υ·Χ + Χ^2 - 1)/(Χ^2·(Υ - Χ))= **
(Χ^2 = 1 - Υ^2)
**=2·(Υ·Χ - Υ^2)/(Χ^2·(Υ - Χ))=
=2·Υ·(Χ - Υ)/(Χ^2·(Υ - Χ))=
=- 2·Υ/Χ^2 = - 2·SIN(x)/COS(x)^2